OPINI PELANGGAN TERHADAP KUALITAS, KENYAMANAN FITUR – FITUR PADA MOBIL HONDA JAZZ DI JAKARTA - Siti Meisyaroh (Jurnal Manajemen, 2017)
The rapid development of automotive industry in Indonesia to make a tight level of competition, especially in the automobile industry. The car manufacturers continue to push the product. This is evident from the diverse array of brands and types of cars in Indonesia.This study sought to determine what factors are affecting the purchasing decisions of Honda Jazz in Jakarta.Keywords: Quality Of Product, Price, Promotion, Brand Awareness, Purchase Decision